2015
DOI: 10.18316/1981-8858.15.10
|View full text |Cite
|
Sign up to set email alerts
|

propriedades Químicas Dos Solos De Uma Sub-Bacia Hidrográfica Sob Processo De Degradação Ambiental

Abstract: RESUMOO manejo inadequado dos solos tem sido a principal causa dos processos erosivos em bacias hidrográficas. Estas áreas apresentam, devido a estes processos, degradação química dos solos decorrente da perda de nutrientes e ausência de adubação. Este trabalho teve por objetivo avaliar o estado de degradação das propriedades químicas dos solos da sub-bacia Dois Córregos. Os solos mais representativos da sub-bacia são o Latossolo Vermelho e o Argissolo Vermelho. As análises foram realizadas em amostras de dez … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
2
0
5

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 12 publications
0
2
0
5
Order By: Relevance
“…Right branches are associated to individual wood volume (IWV) higher than 0.001796m 3 , in which there is the predominance of medium and high classes. On the other hand, in the left branch there is the predominance of medium and low classes related forestry production in acid soils, especially in pH less than 5.0, because it interferes in the fixation of phosphorus, decreases root respiration and interferes in absorption, transportation and in the use of nutrients and water by plants (COSTA et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Right branches are associated to individual wood volume (IWV) higher than 0.001796m 3 , in which there is the predominance of medium and high classes. On the other hand, in the left branch there is the predominance of medium and low classes related forestry production in acid soils, especially in pH less than 5.0, because it interferes in the fixation of phosphorus, decreases root respiration and interferes in absorption, transportation and in the use of nutrients and water by plants (COSTA et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Essa diferença na textura do solo da área de pastagem às demais pode ser atribuída a ação do sistema radicular da vegetação na retenção de partículas do material mineral no caso da capoeira e vegetação de APP, e também, a lixiviação das partículas de silte e argila da camada superficial do solo da pastagem, devido esse receber o maior impacto de gotas de chuva em sua superfície, aumentando expressivamente o escoamento da água (COSTA et al, 2015).…”
Section: Repetições Textura Texturaunclassified
“…O manejo do solo e suas peculiaridades por ser originado em clima tropical deixa-o mais fragilizado à ação do intemperismo físico, como a chuva. Consequentemente a desagregação com o impacto da água sobre sua superfície, faz com que milhares de partículas do colóide se desprendam e sejam arrastadas à parte mais baixa do terreno, iniciando assim a sua degradação (COSTA et al, 2015). Esse tipo de processo de degradação corresponde a erosão hídrica, uma das grandes responsáveis pela degradação de extensas áreas (ESCOBAR et al, 2017).…”
Section: Introductionunclassified
“…Without correcting these soils, eucalyptus, like other crops, has its development impaired, since it finds impediments to the growth of the root system, responsible for the absorption of water and nutrients necessary for the crop cycle, thus affecting productivity (Costa et al, 2015). Lima et al (2013) showed that the physical and chemical attributes of the soil, as well as those related to plants, present spatial variability and that the distance between the samples should be taken into account in the study of these attributes, as recommended by geostatistics.…”
Section: Introductionmentioning
confidence: 99%